Padrões de crescimento diamétrico em comunidades arbóreas com diferentes gradientes de perturbação na Amazônia Central - Brum, Bárbara Nayara Sbardelotto (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
About 1860 trees with dendrometric bands were monitored bi-monthly for a period of two years in a terra firme forest in Central Amazonia, from three different scenarios: secondary forests (capoeiras), forest fragments and continuous forests. The effects of intrannual variations and seasonality on the diametric growth a among the communities were analyzed, correlating them with climatic characteristics (temperature and precipitation), canopy opening, wood density and floristic composition. The differences between the environments were also evaluated regarding the rate of accumulation of biomass associated with the diametric growth of the individuals. The diametric growth was higher in capoeiras when compared to forest fragments and continuous forests. Conversely, the capoeiras had the lowest rate of accumulation of biomass in relation to the others. This difference between capoeiras and other environments is mainly due to the different compositional patterns between them. The wood density and the floristic composition observed in areas of forest fragments and continuous forest were similar while the capoeiras presented different floristic composition, with higher number of low density wood species. Influence of the canopy opening for the increment was similar between the three environments and therefore we infer that its importance for the different diametric growth patterns was of minor importance. The similarity on tree diametric growth and biomass accumulation between fragments and continuous forests indicates that these fragments maintain vegetative patterns similar to pristine forests. Proximity to continuous forests and tree acclimatization capacity in fragmented environments are amongst the possible explanations for this result. Precipitation patterns positively influenced growth and biomass patterns for the three environments and were more important than temperature, although both were not significant. Possibly stronger trends of these variables, especially precipitation, would be observed if the series of growth data were larger than two years. We therefore suggest that changes in rainfall regimes for the Amazon should have important consequences for the biome's role in the accumulation and stock of carbon. These results provide a detailed initial view of the sensitivity of trees to intra annual climate changes in areas with different degree of atropic disturbance and floristic composition. In the long term, this study can provide predictions about the growth response and biomass accumulation in forests that have undergone some degree of disturbance in relation to future climate change scenarios.
Keywords: Crescimento dendrométrico; Gradiente de perturbação; Biomassa; Sazonalidade